Catalytic C–C cross-coupling and hydrogen evolution by two Pd(II)-complexes of di-2-pyridyl ketone benzoyl hydrazones. Issue 13 (3rd July 2019) - Bakir, Mohammed; Lawrence, Mark W.; Nelson, Peter; Yamin, M. Bohari
Abstract: The reactions between [PdCl2 (CH3 CN)2 ] and dpk-h [dpk-h = di-2-pyridyl ketone benzoyl hydrazone (dpkbh) or di-2-pyridyl ketone 4-aminobenzoyl hydrazone (dpk-4-abh)] at room temperature in air produced [PdCl2 (κ 3 -Npy, Nim, O-dpkbh)] (1 ) and PdCl2 (κ 3 -Npy, Nim, O-dpk-4-abh)] (2 ). X-ray structural analysis on a single crystal of PdCl(κ 3 -N, N, O-dpk-4-abh-H)]·H2 O·dmf (3 ) established its authenticity, points to keto-enol tautomerization due to solvent-compound interactions and revealed pseudo-coordination of the carbonyl group to the Pd ion. Solid-state infrared measurements confirmed the pseudo coordination of the carbonyl group of dpk-h as evident from the appearance of the ν(C=O) of coordinated dpk-h in close proximity to the ν(C=O) of uncoordinated dpk-h. 1 H NMR measurements on protophilic solutions of 1 and 2 disclosed solvent dependence and keto-enol tautomerization while variable temperature studies established the predominance of the keto form. The electronic absorption spectra of 1 and 2 measured in protophilic solvents confirmed the coordination of the Pd ion to dpk-h as evident from the appearance of d-d and ligand based electronic transitions. The catalytic C–C cross-coupling reactions and electro-catalytic behavior of 1 and 2 toward a proton reduction were investigated and revealed good catalytic properties. Overall rate constants ( k app ) for the electrocatalytic H2 evolution of (3.39 ± 0.3) × 10 3 and (4.04 ± 0.2) × 10 3 M −1 s −1 were estimated and overpotentials of 157 and 67 mV, and turnover numbers (TON) of 2.0 and 3.2 for 1 and 2, respectively, were determined. Graphical Abstract: